The Effects of Methylphenidate Treatment on Child Growth in Thai Children and Adolescents with Attention-Deficit/Hyperactivity Disorder - Kanchana Koonrungsesomboon (2020)
© Copyright 2020, Mary Ann Liebert, Inc., publishers 2020. Objectives: To determine the effects of methylphenidate treatment on child growth in Thai pediatric patients with attention-deficit/hyperactivity disorder (ADHD). Methods: The medical records of children and adolescents with ADHD, between 5 and 18 years of age, who received pharmacological treatment with methylphenidate as a sole psychiatric medication for ≥1 year between 2001 and 2018 at the Rajanagarindra Institute of Child Development, Thailand, were retrospectively reviewed. Data on anthropometric parameters and methylphenidate use were extracted. Height and weight were converted to age- and gender-corrected standard scores (z-scores) using norms from the Thai pediatric population. Changes in height and weight z-scores were assessed using a paired t-test or one-way repeated measures ANOVA with the Bonferroni correction. Results: In this retrospective observational study, 911 children and adolescents were eligible, with the mean age of 95.0 ± 19.5 months at baseline, the cumulative duration of methylphenidate treatment of 39.4 ± 23.5 months, and the average daily dosage of 14.1 ± 6.2 mg/day. Comparative analysis found no statistically significant change in height z-scores between baseline and last recorded measurement (mean difference = 0.0017, confidence interval [95% CI] = -0.0004 to 0.0038, p = 0.107), while a slight, but significant increase in weight z-scores was observed (mean difference = 0.0271, 95% CI = 0.0179-0.0362, p < 0.001). Longitudinal analysis observed that weight z-scores were significantly decreased during the first year of therapy, but regained in the second year and continued to increase in subsequent years of therapy. Conclusion: Treatment with methylphenidate in our cohort of Thai pediatric patients with ADHD was not associated with growth deficits, except for a slightly significant decrease in weight during the first year of therapy.